Fibroblasts from phenotypically normal palmar fascia exhibit molecular profiles highly similar to fibroblasts from active disease in Dupuytren's Contracture - Satish Latha; LaFramboise William A; Johnson Sandra; Vi Linda; Njarlangattil Anna; Raykha Christina; Krill-Burger John Michael; Gallo Phillip H; O'Gorman David B; Gan Bing; Baratz Mark E; Ehrlich Garth D; et al. (BMC, 2012)
Abstract Background Dupuytren's contracture (DC) is a fibroproliferative disorder characterized by the progressive development of a scar-like collagen-rich cord that affects the palmar fascia of the hand and leads to digital flexion contractures. DC is most commonly treated by surgical resection of the diseased tissue, but has a high reported recurrence rate ranging from 27% to 80%. We sought to determine if the transcriptomic profiles of fibroblasts derived from DC-affected palmar fascia, adjacent phenotypically normal palmar fascia, and non-DC palmar fascial tissues might provide mechanistic clues to understanding the puzzle of disease predisposition and recurrence in DC. Methods To achieve this, total RNA was obtained from fibroblasts derived from primary DC-affected palmar fascia, patient-matched unaffected palmar fascia, and palmar fascia from non-DC patients undergoing carpal tunnel release (6 patients in each group). These cells were grown on a type-1 collagen substrate (to better mimic their in vivo environments). Microarray analyses were subsequently performed using Illumina BeadChip arrays to compare the transcriptomic profiles of these three cell populations. Data were analyzed using Significance Analysis of Microarrays (SAM v3.02), hierarchical clustering, concordance mapping and Venn diagram. Results We found that the transcriptomic profiles of DC-disease fibroblasts and fibroblasts from unaffected fascia of DC patients exhibited a much greater overlap than fibroblasts derived from the palmar fascia of patients undergoing carpal tunnel release. Quantitative real time RT-PCR confirmed the differential expression of select genes validating the microarray data analyses. These data are consistent with the hypothesis that predisposition and recurrence in DC may stem, at least in part, from intrinsic similarities in the basal gene expression of diseased and phenotypically unaffected palmar fascia fibroblasts. These data also demonstrate that a collagen-rich environment differentially alters gene expression in these cells. In addition, Ingenuity pathway analysis of the specific biological pathways that differentiate DC-derived cells from carpal tunnel-derived cells has identified the potential involvement of microRNAs in this fibroproliferative disorder. Conclusions These data show that the transcriptomic profiles of DC-disease fibroblasts and fibroblasts from unaffected palmar fascia in DC patients are highly similar, and differ significantly from the transcriptomic profiles of fibroblasts from the palmar fascia of patients undergoing carpal tunnel release.